Blues deluxe. Vol. 2 [compact disc] - Bonamassa, Joe (J&R Adventures, 2023)
Twenty years since the release of his best-selling album Blues Deluxe, which celebrated "the year of the blues" with unforgettable reinterpretations of classic tracks, Joe Bonamassa is taking stock of how far he and the genre have come with Blues Deluxe Vol. 2 Featuring two new originals and eight new covers of some of the most influential names in the blues, Bonamassa returns to his roots and gives new life to the classic tracks that have informed his own artistry.